Mandibular Rim Trilogy with Botulinum Toxin Injection: Reduction, Projection, and Lift - Zhou, Renpeng; Pan, Benyun; Wang, Chen; Wang, Danru (Facial Plastic Surgery, 2017)
“Onabotulinum toxin A (Botox) revolution” has brought the fundamental change in the facial rejuvenation as well as the concept of microinjection. The aesthetic standard tends to be the “globalization”; however, Asians have different aesthetic cultures and unique facial features compared with Caucasians. A new rejuvenation concept is proposed during our practice; the Asian face should preserve the original facial identity during Botox treatments. The lower face is treated with botulinum toxin to achieve a harmonious facial profile. Twenty young females ranging in age from 30 to 45 years consented and received the three-pronged procedure from March 2014 to April 2015; photography at baseline and follow-up visit were taken and analyzed. After posttreatment for 2 months, significant improvement was observed compared with the baseline. And the reduced masseter prominence and prominent chin were obtained, showing a favorable facial contour and harmonious appearance during the follow-up. The novel three-pronged approach to lower facial rejuvenation was aimed at the Asian characteristic of hypertrophic masseter, chin retrusion, and the facial sagging during the aging process. Botox treatment was a quite effective and safe strategy to improve the appearance and contour of the lower face in Asian patients.
Keywords: onabotulinum toxin A (Botox); lower face; rejuvenation; contour; Asian